Determination of Oxalid Acid in Green Spinach (Amaranthus Gangeticus) An Red Spinach (Amaranthus Spinousus) Using Spectrophotometry Method: Penentuan Kadar Asam Oksalat pada Bayam Hijau (Amaranthus Gangeticus) dan Bayam Merah (Amaranthus Spinousus) Menggunakan Metode Spektrofotometri - Agustin Puspitasari; Argoto Mahayana (Jurnal Kimia dan Rekayasa, 2021)
Spinach (Amaranthus sp.) is a plant that has a taproot root system with elliptic branches that spread out in all directions. Oxalic acid is a dicarboxylic acid which only consists of two C atoms in each molecule, so that the two carboxylic groups are side by side.Determination of oxalic acid levels is done by boiling green and red spinach then spinach leaves are drained for 20 minutes and weighed 2.5 grams and then mashed and added with aquabidest then in a centrifuge. 250 mL of spinach cooking water is weighed and centrifuged. Each sample was then placed into a 500 mL volumetric flask and analyzed spectrophotometrically.The results of the analysis of oxalic acid levels in green spinach and red spinach were 52.2729 ppm on green spinach leaves at 0 hours; 62,5643 ppm when the leaves of green spinach are allowed to stand for 6 hours; 78,9687 ppm in green spinach water at 0 hours; 82.7573 ppm when the green spinach water is allowed to stand for 6 hours; 46,7323 ppm on red spinach leaves at 0 hours; 61,8247 ppm when the leaves of red spinach are allowed to stand for 6 hours; 61.8247 ppm in red spinach vegetable water at 0 hours and 122.66852 ppm when red spinach vegetable water was allowed to stand for 6 hours. AbstrakBayam (Amaranthus sp.) merupakan tumbuhan yang memiliki sistem perakaran tunggang dengan cabang berbentuk elips yang menyebar ke segala arah. Asam oksalat merupakan asam dikarboksilat yang hanya terdiri dari dua atom C pada setiap molekulnya, sehingga kedua gugus karboksilat tersebut berdampingan.Penentuan kadar asam oksalat dilakukan dengan cara merebus bayam hijau dan merah kemudian daun bayam ditiriskan selama 20 menit dan ditimbang 2,5 gram kemudian dihaluskan dan ditambahkan aquabidest kemudian di centrifuge. 250 mL air rebusan bayam ditimbang dan disentrifugasi. Masing-masing sampel kemudian dimasukkan ke dalam labu takar 500 mL dan dianalisis secara spektrofotometri.Hasil analisis kadar asam oksalat pada bayam hijau dan bayam merah sebesar 52,2729 ppm pada daun bayam hijau pada jam ke-0; 62.5643 ppm bila daun bayam hijau didiamkan selama 6 jam; 78,9687 ppm dalam air bayam hijau pada 0 jam; 82,7573 ppm bila air kangkung didiamkan selama 6 jam; 46,7323 ppm pada daun bayam merah pada 0 jam; 61,8247 ppm bila daun bayam merah didiamkan selama 6 jam; 61,8247 ppm pada air sayur bayam merah pada 0 jam dan 122,66852 ppm pada air sayur bayam merah didiamkan selama 6 jam.